Keywords for Latina/o studies - Vargas, Deborah R.; Mirabal, Nancy Raquel, 1966-; La Fountain-Stokes, Lawrence M. (Lawrence Martin), 1968- (Keywords Ser., 2017)
The keywords included in this text represent established and emergent terms, categories, and concepts that undergird Latina/o studies; they delineate the shifting contours of a field best thought of as an intellectual imaginary and experiential project of social and cultural identities within the U.S. academy. Bringing together sixty-three essays, from humanists, historians, anthropologists, sociologists, among others, each focused on a single term, the volume reveals the broad range of the field while also illuminating the tensions and contestations surrounding issues of language, politics, and histories of colonization, specific to this area of study. From "borderlands" to "migration," from "citizenship" to "mestizaje," this volume will be informative for those who are new to Latina/o studies, providing them with a mapping of the current debates and a trajectory of the development of the field, as well as being a valuable resource for scholars to expand their knowledge and critical engagement with the dynamic transformations in the field